Women Designers and the Restoration of Historic Buildings in 20th century Italy - Caterina Giannattasio; Donatella Rita Fiorino (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
This research investigates the contribution offered by some female figures in the field of architecture during the period between the Second World War and the seventies of the 20th century. Belonging to three separate but often connected worlds - academic, institutional and professional - they are Margherita Asso, Gae Aulenti, Lina Bo Bardi, Cini Boeri, Graziana Del Guercio Barbato, Liliana Grassi, Franca Helg and Egle Renata Trincanato, operating in national context, excepted for Lina Bo Bardi, Brazilian by adoption. The study starts from the general issues related to the affirmation of women in employment, analysing the actions taken by Associations since the end of the 19th century, further developed thanks to events, as well as cultural and social projects until today. In addition, the investigation focuses on the comparison between the eight selected ladies: belonging to different geographical, educational, cultural and professional contexts, they act in a particularly sensitive time in the 20th century, telling us “another story”, seen through the lens of women. By means of a detailed and careful consideration of both the theoretical and practical point of view, taking into account their scientific production and design, the research brings out their lively and active participation in the debate following the Reconstruction, as well as their significant contribution to reflections on projects specifically carried out on architectural heritage.